Manipulating ultrasonic non-contact levitation technique - Koh, Weiheng (Nanyang Technological University, 2024)
Ultrasonic levitation is a fascinating technology with a wide range of applications across various fields. The principle behind ultrasonic levitation involves the use of ultrasonic waves at high frequencies to generate acoustic radiation pressure (net pressure exerted on a surface by acoustic waves) to counteract the gravitational force on an object. This allows for the suspension of objects in mid-air without any physical contact. The ability to model an ultrasonic non-contact levitation device that can manipulate millimetre-scale objects opens possibilities for applications in fields such as materials science, biology, and even manufacturing. The precise control over the levitated objects, including picking up, self-centering, orientation, translation, and release, makes it a versatile tool for various purposes. One significant advancement in ultrasonic levitation technology is the capability to not only suspend objects but also rotate and translate them in three-dimensional spaces. This enhancement in functionality expands the potential applications of ultrasonic levitation, making it useful for tasks that require intricate manipulation and positioning of objects. Furthermore, the ability to levitate objects larger than the acoustic wavelength is a noteworthy development. This is achieved by adjusting variables such as phase shift angles. While ultrasonic levitation has shown great promise, challenges such as levitating different objects of shapes, sizes and mass remain areas of active research. Thus, ongoing research aims to address these challenges and potentially unlock more possibilities on this contactless manipulation technique, paving the way for innovative applications in fields like transportation, assembly, and medical procedures.